2013
DOI: 10.1080/03601234.2014.858007
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and histopathological changes in silver catfishRhamdia quelen(Siluriformes) exposed to clomazone herbicide in the Madre River, Santa Catarina State, Southern Brazil

Abstract: This study evaluated the influence of the clomazone herbicide (2-[(2-chlorophenyl)methyl]-4,4-dimethyl-3-isoxazolidinone) contamination on the hematological parameters and histological changes in gills and liver of silver catfish (Rhamdia quelen) from Madre River, Santa Catarina State, Southern Brazil. Fish were collected between March 2010 and January 2012 at two different sites of the Madre River, one site receiving residual water (contaminated site) from rice culture (n=49) and another that do not receive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It is possible that despite the long evolution chain to reach the freshwater habitat, P. motoro still preserve the liver morphology of the marine elasmobranchs. Brum et al (2014) showed that silver catfish exposed to water from a polluted river (Madre) in Southern Brazil presented higher percentage of inflammatory cells in blood comparing to control group. In our study, 69.2 % of the fish samples presented large number of lymphocytes in the spleen and 23.1 % hyperemia comparing within the group (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It is possible that despite the long evolution chain to reach the freshwater habitat, P. motoro still preserve the liver morphology of the marine elasmobranchs. Brum et al (2014) showed that silver catfish exposed to water from a polluted river (Madre) in Southern Brazil presented higher percentage of inflammatory cells in blood comparing to control group. In our study, 69.2 % of the fish samples presented large number of lymphocytes in the spleen and 23.1 % hyperemia comparing within the group (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…One of the most prominent alterations of the liver is the presence of lipidosis or steatosis, which are diagnosed by the accumulation of lipids in vacuoles of varying size found in the cytoplasm of the hepatocytes (Brum et al, 2014). Micro‐ and macrolipidosis has been found in the hepatocytes of catfish ( Rhamdia quelen ) exposed to the commercial formula of clomazone (Brum et al, 2014) and of carp ( Cyprinus carpio ) exposed to different concentrations of nanoparticles of TiO 2 (Federici et al, 2007; Linhua et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that can significantly affect hematological parameters in teleosts include reproductive cycle, diet, temperature, pH and photoperiod (Sandnes et al, 1988;Kavadias et al, 1996;Svoboda et al, 2001;Guijarro et al, 2003;Kavadias et al, 2003;Bayir, 2005), or stress, pollution, parasitism, size, seasonal variations (Clarks et al, 1979;Barham et al, 1980;Ranzani-Paiva et al, 2004;Camargo et al, 2005;Santos et al, 2009;Onyia et al, 2013;De Souza Neves et al, 2014;Brum et al, 2014;Figueiredo et al, 2014;Fallah et al, 2014).…”
Section: Samplingmentioning
confidence: 99%